Total Phenolic Content Analysis, Antioxidant Activity, and Isolation of Phenolic Acid Compounds from Methanol Extract of Celery (Apium graveolens L.) - Rahma Farida Hanum; Enny Fachriyah; Ismiyarto Ismiyarto; Purbowatiningrum Ria Sarjono (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2025)
Celery (Apium graveolens L.), a member of the Apiaceae family, is rich in bioactive compounds and exhibits various health benefits, including antihypertensive, antibacterial, anti-inflammatory, and antioxidant activities. The presence of diverse phenolic acids, as identified in previous studies, prompted this research to analyze the total phenolic content, evaluate antioxidant activity, and isolate phenolic acids from the methanol extract of celery. The study involved phytochemical screening, maceration extraction, determination of total phenolics using the Folin–Ciocalteu method, antioxidant testing via the DPPH method, and phenolic acid isolation using three approaches: base hydrolysis (HB), acid hydrolysis (HA), and non-hydrolysis (TH). The isolates were analyzed using UV–Vis spectrophotometry, CMS, and LC/MS-MS QTOF. The methanol extract of celery yielded 16.59% and was found to contain flavonoids, phenolic acids, saponins, tannins, and steroids. The total phenolic content was 17.268 ± 0.057 mg GAE/g extract, while the IC50 value was 1712.782 ± 0.115 mg/L, indicating very weak antioxidant activity. Isolation of phenolic acids revealed that the HA fraction contained pyrogallol and caffeic acid. This was supported by the A3 band (λmax 230 nm and 269 nm) with a molecular weight of 126 m/z, characteristic of pyrogallol. The A4 band (λmax 218, 242, 298, and 325 nm) with a molecular weight of 180.0387 m/z was characteristic of caffeic acid.